Schisandrin B Prevents Hind Limb from Ischemia-Reperfusion-Induced Oxidative Stress and Inflammation via MAPK/NF-κB Pathways in Rats. (19th June 2017) - Zhu, Ning; Cai, Changhong; Zhou, Aiming; Zhao, Xuyong; Xiang, Yijia; Zeng, Chunlai
Abstract : Schisandrin B (ScB), isolated from Schisandra chinensis ( S. chinensis ), is a traditional Chinese medicine with proven cardioprotective and neuroprotective effects. However, it is unclear whether ScB also has beneficial effects on rat hind limb ischemia/reperfusion (I/R) injury model. In this study, ScB (20 mg/kg, 40 mg/kg, and 80 mg/kg) was administered via oral gavage once daily for 5 days before the surgery. After 6 h ischemia and 24 h reperfusion of left hind limb, ScB reduced I/R induced histological changes and edema. ScB also suppressed the oxidative stress through decreasing MDA level and increasing SOD activity. Moreover, above changes were associated with downregulated TNF- α mRNA expression and reduced level of IL-1β in plasma. Meanwhile, ScB treatment downregulated activation of p38MAPK, ERK1/2, and NF- κ B in ischemic skeletal muscle. These results demonstrate that ScB treatment could prevent hind limb I/R skeletal muscle injury possibly by attenuating oxidative stress and inflammation via p38MAPK, ERK1/2, and NF- κ B pathways.